Current advancements in the management of giant cell arteritis. (August 2009) - Ghosh, Parasar; Borg, Frances A; Dasgupta, Bhaskar
Giant cell arteritis (GCA) is a vasculitis of large and medium-sized vessels that predominantly affects the elderly. GCA should be recognized as a medical emergency owing to its associated critical ischemia, which frequently causes neuro-ophthalmic complications. The pathogenesis of GCA is unclear, but it is speculated that the disease process is triggered by an infectious agent or an autoantigen (through molecular mimicry) being sensed by Toll-like receptors on immature dendritic cells in the tunica adventitia of arteries. Dendritic cells then present antigen to CD4 + T cells leading to T-cell proliferation and cytokine release, activation of macrophages and formation of granulomata-containing giant cells, with injury to the arterial wall by matrix metalloproteinases, reactive oxygen and nitrogen intermediates. Reparative processes then cause revascularization and intimal hyperplasia. This results in vascular occlusion and consequent tissue ischemia. Features predictive of visual loss in GCA include jaw claudication, diplopia and temporal artery abnormalities on physical examination. Modern imaging with duplex ultrasonography and fluorodeoxyglucose positron emission tomography shows promise for early diagnosis and detection of major artery involvement in GCA. However, temporal artery biopsy remains the gold-standard investigation. Early recognition and urgent institution of high-dose corticosteroids is the mainstay of treatment. Studies have found mixed experiences of using conventional disease-modifying drugs and biological therapies. Furthermore, evaluation of their steroid-sparing potential is required with well-constructed, randomized, controlled trials.